Amygdala volumetry in "imaging-negative" temporal lobe epilepsy. Issue 9 (21st August 2003) - Bower, S P C; Vogrin, S J; Morris, K; Cox, I; Murphy, M; Kilpatrick, C J; Cook, M J
Abstract : Objective: Although amygdala abnormalities are sometimes suspected in "imaging-negative" patients with video EEG confirmed unilateral focal epilepsy suggestive of temporal lobe epilepsy (TLE), amygdala asymmetry is difficult to assess visually. This study examined a group of "imaging-negative" TLE patients, estimating amygdala volumes, to determine whether cryptic amygdala lesions might be detected. Methods: Review of video EEG monitoring data yielded 11 patients with EEG lateralised TLE and normal structural imaging. Amygdala volumes were estimated in this group, in 77 patients with pathologically verified hippocampal sclerosis (HS), and in 77 controls. Results: Seven of 11 "imaging-negative" cases had both significant amygdala asymmetry and amygdala enlargement, concordant with seizure lateralisation. Although significant amygdala asymmetry occurred in 35 of 77 HS patients, it was never attributable to an abnormally large ipsilateral amygdala. Compared with patients with HS, patients with amygdala enlargement were less likely to have suffered secondarily generalised seizures (p<0.05), and had an older age of seizure onset (p<0.01). Conclusion: Abnormal amygdala enlargement is reported in seven cases of "imaging-negative" TLE. Such abnormalities are not observed in patients with HS. It is postulated that amygdala enlargement may be attributable to a developmental abnormality or low grade tumour. It is suggested that amygdala volumetry is indicated in the investigation and diagnosis of "imaging-negative" TLE.